2006
DOI: 10.1159/000092705
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 5 Plays an Essential Role in Elicitation of Contact Sensitivity through Dual Effects on Eosinophils and B-1 Cells

Abstract: Background: Elicitation of contact sensitivity (CS) depends on B-1-cell-derived antigen-specific immunoglobulin M (IgM) antibodies that recruit CS effector T cells into the local tissue, which is followed by infiltration of antigen-nonspecific mononuclear cells and polymorphonuclear cells, such as neutrophils and eosinophils. In this study, we investigated the role of interleukin (IL)-5, which has broad effects on both eosinophils and B-1 cells, in elicitation of CS. Methods: IL-5 receptor α-chain-deficient (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
(35 reference statements)
0
15
0
Order By: Relevance
“…The process is likely to involve the enhanced IgM response since B1 cell-derived haptenspecific IgM are critically required for the initiation of CS by forming an immune complex and triggering the recruitment of Agspecific T cells (11). Furthermore, IL-5 is required for the elicitation of CS by enhancing B1 and eosinophil functions (44). Our results therefore provide an upstream event by which B1 cells are activated for CS.…”
Section: Discussionmentioning
confidence: 70%
“…The process is likely to involve the enhanced IgM response since B1 cell-derived haptenspecific IgM are critically required for the initiation of CS by forming an immune complex and triggering the recruitment of Agspecific T cells (11). Furthermore, IL-5 is required for the elicitation of CS by enhancing B1 and eosinophil functions (44). Our results therefore provide an upstream event by which B1 cells are activated for CS.…”
Section: Discussionmentioning
confidence: 70%
“…Production of Th2-type cytokines by ␣␤ T cells may well contribute to disease, as IL-5 production has been linked to recruitment of B1 IgM-producing cells to local tissue, which together with eosinophil recruitment can result in contact sensitivity. 53 It is likely that local dysregulation of cytokine production is important for disease induction, and resident innate cells may well be important contributors to this process.…”
Section: Discussionmentioning
confidence: 99%
“…While the reaction to oxazolone is predominantly a Th1-dependent response in which both TNF-a and IFN-c have been shown to play a role, multiple other cytokines such as IL-4, IL-10 and IL-6 have also been shown to participate in this response [26,[35][36][37][38]. Previous studies have suggested that TNF-a is the main inflammatory cytokine, as blockade of TNF-a prevented the CS response, while IFN-c blockade only had a partial protective effect [35,36].…”
Section: Discussionmentioning
confidence: 99%